2021
DOI: 10.56454/inbj9899
|View full text |Cite
|
Sign up to set email alerts
|

Fourier Transform Infrared Spectroscopic Analysis in Applied Cotton Fiber and Cottonseed Research: A Review

Abstract: Cotton, one of the most important and widely grown crops in the world, is a well-traded agricultural commodity primarily for textile fiber purposes. In addition, cottonseed (a byproduct of fiber production) has been used as an agro-based raw material for manufacturing bio-friendly and sustainable products. Qualitative and quantitative characterization of cotton biomass products/byproducts is an important research area for quality monitoring, improvement, and enhanced use. Fourier transform infrared (FT-IR) spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 84 publications
3
17
0
Order By: Relevance
“…The spectra are given in Figure 1 . The IR spectra of various cotton-related materials have been previously reported (e.g., [ 23 , 43 , 44 , 45 ]). The ATR spectrum of the CSM surface ( Figure 1 , top spectrum) showed a strong and broad band at 3700–3000 cm −1 due to the O-H and N-H stretching in carbohydrates, glycerol, adsorbed water, and protein.…”
Section: Resultsmentioning
confidence: 99%
“…The spectra are given in Figure 1 . The IR spectra of various cotton-related materials have been previously reported (e.g., [ 23 , 43 , 44 , 45 ]). The ATR spectrum of the CSM surface ( Figure 1 , top spectrum) showed a strong and broad band at 3700–3000 cm −1 due to the O-H and N-H stretching in carbohydrates, glycerol, adsorbed water, and protein.…”
Section: Resultsmentioning
confidence: 99%
“…ATR–FTIR analysis has been used in cotton biomass characterization [ 35 , 36 , 37 ]. The ATR–FTIR spectra of the oil extracts of the cottonseed butters ( Figure 2 ) were typical to those of cottonseed and other vegetable oil samples in the literature [ 7 , 35 , 38 ]. The four major peaks were found at 2924, 2854, 1744, and 1160 cm −1 .…”
Section: Resultsmentioning
confidence: 99%
“…The authors also demonstrated that the RS approach was as accurate as near‐infrared analysis. Currently, there are only limited reports on RS characterization of fiber and cottonseed research (Cabrales et al., 2014; da Mata et al., 2022) even though various IR techniques have been applied into a wide array of cotton biomass characterization (He & Liu, 2021; He, Liu et al., 2022; Liu et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Like infrared spectroscopy (IR), Raman spectroscopy (RS) is a vibrational spectroscopic technique. While IR is an excellent tool for structural and quantitative analysis of natural products (Di Meo et al., 2022; He & Liu, 2021; He & Ohno, 2012), RS is able to provide some additional structural information due to the different detection mechanisms (Johnston & Aochi, 1996; Makarem et al., 2019). For example, unlike IR, RS is a good technique for analyzing alkyl chains since the C─C and C─H bonding can be determined in the presence of water (Özgenç et al., 2017).…”
Section: Introductionmentioning
confidence: 99%